Clinging to closeness: The parental view on developing a close bond with their infants in a NICU. (July 2018) - Mäkelä, Heli; Axelin, Anna; Feeley, Nancy; Niela-Vilén, Hannakaisa
Highlights: Infant's NICU stay provided an emotional rollercoaster ride to the parents. Moments together as a family in the NICU represented normal parenthood. Infant's reciprocal behaviour was significant to parents' closeness experiences. Stored closeness sustained parents through the unavoidable separation. Abstract: Objective: To identify and understand how parents develop a close bond to their infants in the neonatal intensive care unit (NICU). Design: A qualitative descriptive study; closeness and separation stories recorded in a smartphone application by the parents were analyzed using thematic analysis. Setting and participants: Twenty-three parents of nineteen infants who were taken care of in a level III NICU in Finland. Findings: Bonding moments and a disrupted dyadic parent-infant relationship continuously alternated as in a rollercoaster ride during the hospital stay. Transitions from closeness to separation and vice versa were the most emotional stages on the journey. Parents had a natural desire to be close and create a bond with their infants; however, they accepted the separation as part of NICU care. Key conclusions: The findings indicate that closeness with their infant was the power that parents stored and that led them through unavoidable separation to normal parenthood. Implications for practice: Bonding and attachment will occur naturally if parents are close to their infants and permitted privacy and time with their infants. NICU staff should create a peaceful and calming environment that enables and supports this bonding process.